PENGARUH WAKTU DAN SUHU STERILISASI TERHADAP KANDUNGAN PROKSIMAT IKAN BANDENG (Chanos chanos) KALENG - Muhammad Maskur (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
This study aims to determine the exact combination of time and temperature of sterilization to the proximate content of canned milkfish. Where the time combination used are 60 minutes, 75 minutes, and 90 minutes. Combination of temperature used are 110OC, 115 OC, and 120 OC. This research was conducted from Januari – Juni 2017 in two locations, namely in the Workshop Teaching Factory SUPM Bone dan BPPMHP Makassar. Sampling taken from canned milkfish randomly in each treatment. The data were analyzed by using ANOVA statistical analysis and next the significant parameter were tested using Tuckey and then explained by using table. The research results that the combination of temperature and time of sterilization had a significant effect on the quality of canned milkfish. Where temperature treatment 110 OC and time of 75 minutes has the best proximate content (best nutrition).